2004
DOI: 10.1161/01.cir.0000105700.95607.49
|View full text |Cite
|
Sign up to set email alerts
|

Estradiol and Progestins Differentially Modulate Leukocyte Infiltration After Vascular Injury

Abstract: Background-Inflammation plays an important role in the response to endoluminal vascular injury. Estrogen (17␤-estradiol, E 2 ) inhibits neointima formation in animal models, and the progestin medroxyprogesterone acetate (MPA) blocks this effect. This study tested the hypothesis that E 2 inhibits the migration of inflammatory cells, particularly granulocytes, into the rat carotid arteries after acute endoluminal injury and that MPA blocks this effect. Methods and Results-Ovariectomized rats were randomly divide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
1
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(92 citation statements)
references
References 44 publications
2
87
1
2
Order By: Relevance
“…This injury to the carotid artery is associated with infiltration of leukocytes including phagocytes, granulocytes, and lymphocytes in the adventitia surrounding the site of injury [53,54]. Ovariectomized rats have a significant leukocyte infiltrate following arterial injury [55]. Consistent with this observation, estrogen treatment of OVX rats yielded a decrease in migration of neutrophils and monocytes into the damaged artery, suggesting a protective effect [55].…”
Section: Neutrophilsmentioning
confidence: 75%
See 1 more Smart Citation
“…This injury to the carotid artery is associated with infiltration of leukocytes including phagocytes, granulocytes, and lymphocytes in the adventitia surrounding the site of injury [53,54]. Ovariectomized rats have a significant leukocyte infiltrate following arterial injury [55]. Consistent with this observation, estrogen treatment of OVX rats yielded a decrease in migration of neutrophils and monocytes into the damaged artery, suggesting a protective effect [55].…”
Section: Neutrophilsmentioning
confidence: 75%
“…Ovariectomized rats have a significant leukocyte infiltrate following arterial injury [55]. Consistent with this observation, estrogen treatment of OVX rats yielded a decrease in migration of neutrophils and monocytes into the damaged artery, suggesting a protective effect [55]. In the rat model of acute vascular injury, expression of mRNA in the common carotid artery for adhesion molecules P-selectin, vascular cell adhesion molecule-1, and ICAM-1, as well as chemoattractants CINC-2β and monocyte chemoattractant protein-1 (MCP-1), are increased in injured arteries of OVX rats at 2 hours.…”
Section: Neutrophilsmentioning
confidence: 99%
“…Progesterone has reported to block the effect of estrogen. 17,18 Therefore, there is a possibility that progesterone plays some role in the enhancement of vascular remodeling in ovariectomized mice. However, our group has previously reported that increased neointimal formation, DNA synthesis, and atherosclerotic lesions in ovariectomized mice were reversed by treatment with estrogen to the physiologic (female) level, 9,10 suggesting that estrogen contributes to improvements in vascular remodeling over and above the apparent opposite effects of progesterone.…”
Section: Discussionmentioning
confidence: 99%
“…In injured brain, coadministration of MPA with CEE may reverse estrogen's favorable effects on migratory inflammatory cells and potentiate vascular endothelial disruption (Xing et al, 2004) or heighten glutamate-induced excitotoxic injury (Nilsen and Brinton, 2002a, b). Alternatively, it is possible that subcortical brain regions may be more dependent on blood flow, making striatum more susceptible to postischemic vascular obstruction.…”
Section: Discussionmentioning
confidence: 99%